Near-asteroids spacecraft hovering control: a model-free approach with appointed-time performance guarantees - Sun, Ran; Lu, Ruiqiu; Zhang, Chengxi; Wang, Wei; Varatharajoo, Renuganth; Xu, Dezhi (Elsevier, 2025)
This study addresses the challenge of spacecraft hovering near asteroids with unknown dynamics and proposes a model-free control solution with adjustable performance. A backstepping-like control law is developed to ensure tailored settling time and steady-state accuracy for space operations, overcoming the limitations of model-dependent methods in uncertain environments. To improve practicality, a noise-suppression strategy is implemented through a real-time signal differentiation, enabling a robust hovering control even in the presence of navigation sensor interference. Crucially, the approach ensures operational reliability in scenarios ranging from partially known to completely unknown asteroid characteristics, significantly simplifying the implementation for operations around uncharted asteroids. Numerical simulations confirm that the controller can achieve hovering near asteroids with the expected steady-state performance within a predefined time. Compared to conventional model-dependent methods, this approach fundamentally eliminates the need for explicit knowledge of asteroid dynamics, while maintaining its control stability in unknown environments.